SEPARATE ASPECTS OF THE CONTENT AND CONCLUSION OF CONTRACTS FOR THE PERFORMANCE OF SURVEYING WORKS - Yuliya P. Berezina (Russian Studies in Law and Politics)
Contracts of the performance of surveying works (provision of services) are concluded by subsoil users in the process of mining. The contract under study is a civil law nature, despite the fact that the results of contract work and services rendered are used in the public sphere. The quality of surveying work performance affects the safety of mining operations and the financial result of the subsoil user-customer.